Illumina and Nanopore sequencing in culture-negative samples from suspected lower respiratory tract infection patients - Ma, Lichao; Zhu, Chi; Yan, Tianli; Hu, Yun; Zhou, Juan; Li, Yajing; Du, Furong; Zhou, Jianping (Frontiers in Cellular and Infection Microbiology, 2024)
Objective: To evaluate the diagnostic value of metagenomic sequencing technology based on Illumina and Nanopore sequencing platforms for patients with suspected lower respiratory tract infection whose pathogen could not be identified by conventional microbiological tests.: Patients admitted to Respiratory and Critical Care Medicine in Shanghai Ruijin Hospital were retrospectively studied from August 2021 to March 2022.Alveolar lavage or sputum was retained in patients with clinically suspected lower respiratory tract infection who were negative in conventional tests. Broncho-alveolar lavage fluid (BALF) samples were obtained using bronchoscopy. Samples collected from enrolled patients were simultaneously sent for metagenomic sequencing on both platforms.Results: 38 patients with suspected LRTI were enrolled in this study, including 36 parts of alveolar lavage and 2 parts of sputum. According to the infection diagnosis, 31 patients were confirmed to be infected with pathogens, while 7 patients were diagnosed as non-infectious disease. With regard to the diagnosis of infectious diseases, the sensitivity and specificity of Illumina and Nanopore to diagnose infection in patients were 80.6% vs. 93.5%, 42.9 vs 28.6%, respectively. In patients diagnosed with bacterial, mycobacterium and fungal infections, the positive rates of Illumina and Nanopore sequencer were 71.4 %vs 78.6%, 36.4% vs 90.9%, and 50% vs 62.5%, respectively. In terms of pathogen diagnosis, the sensitivity and specificity of pathogens detected by Illumina and Nanopore were 55.6% vs 77.8%, 42.9% vs28.6%, respectively. Among the patients treated with antibiotics in the last two weeks, 61.1% (11/18) and 77.8% (14/18) cases of pathogens accurately detected by Illumina and Nanopore were respectively, among which 8 cases were detected jointly.The consistency between Illumina and diagnosis was 63.9% (23/36), while the consistency between Nanopore and diagnosis was 83.3% (30/36). Between Illumina and Nanopore sequencing methods, the consistent ratio was 55% ( 22/42) based on pathogens diagnosis. Conclusion: Both platforms play a certain value in infection diagnosis and pathogen diagnosis of CMTs negative suspected LRTI patients, providing a theoretical basis for clinical accurate diagnosis and symptomatic treatment. The Nanopore platform demonstrated potential advantages in the identification of mycobacterium and could further provide another powerful approach for patients with suspected mycobacterium infection.